Reconciliation As An Eye-Wash: A Critical Reading of Alexis Wright’s Carpentaria - Jitender Singh (International Journal of Advanced Science and Technology, 2020)
The Aboriginal community was quite happy and hopeful about the policy of reconciliation when it was started by the Australian government in 1991. A number of writers talked about it and so did Alexis Wright in her Plains of Promise which was published in 1997. But soon, through her second novel Carpentaria, she expressed that the policy was merely an eye-wash and did nothing better for the needy. The novel clearly shows that the signs of racism could still be noticed strongly in the tiny towns like Desperance. Everyone was thinking that the policy of reconciliation would make the lives of Aborigines better but the policy proved against it because still the whites were not giving human status to the Aborigines. Even today, the Aborigines are a victim of the racist policies brought by the whites. Moreover, Carpentaria shows that the faulty policy of reconciliation was prepared centering the oppressors rather than the oppressed. That’s why the policy of reconciliation didn’t improve anything on the part of the Aborigines and proved only an eye-wash.